2017
DOI: 10.1186/s12876-017-0655-0
|View full text |Cite
|
Sign up to set email alerts
|

A case report of prostate cancer metastasis to the stomach resembling undifferentiated-type early gastric cancer

Abstract: BackgroundOccurrence of metastatic cancer to the stomach is rare, particularly in patients with prostate cancer. Gastric metastasis generally presents as a solitary and submucosal lesion with a central depression.Case presentationWe describe a case of gastric metastasis arising from prostate cancer, which is almost indistinguishable from the undifferentiated-type gastric cancer. A definitive diagnosis was not made until endoscopic resection. On performing both conventional and magnifying endoscopies, the lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…However, the IHC analyses of the resected tumor revealed that tumor was positive for other markers of prostate cancer, such as AMACR, prostate-specific acid phosphatase (PSAP), androgen receptor, and ERG, suggesting that the tumor was not primary gastric cancer but a metastatic lesion of prostate cancer. There was only one previous case of metastatic gastric metastasis of prostate cancer, which was negative for PSA, similar to our case [12], suggesting that PSA staining was not enough to differentiate the prostate cancer from other cancers. Also, these cases suggest that it is important to perform IHC of the preoperative biopsy sample with multiple markers when the metastatic cancer cannot be denied based on the medical history.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…However, the IHC analyses of the resected tumor revealed that tumor was positive for other markers of prostate cancer, such as AMACR, prostate-specific acid phosphatase (PSAP), androgen receptor, and ERG, suggesting that the tumor was not primary gastric cancer but a metastatic lesion of prostate cancer. There was only one previous case of metastatic gastric metastasis of prostate cancer, which was negative for PSA, similar to our case [12], suggesting that PSA staining was not enough to differentiate the prostate cancer from other cancers. Also, these cases suggest that it is important to perform IHC of the preoperative biopsy sample with multiple markers when the metastatic cancer cannot be denied based on the medical history.…”
Section: Discussionsupporting
confidence: 78%
“…Metastatic gastric tumor of prostate cancer is rare and only 13 cases have been reported to date [2][3][4][5][6][7][8][9][10][11][12][13][14]. Time to metastasis to the stomach from a diagnosis of primary prostate cancer varies (identified simultaneously to 10 years later).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When an SMT-like lesion is encountered in clinical practice, we should consider the possibility of GC and carefully differentiate it from other submucosal lesions, such as gastric neuroendocrine tumors (GI-NETs)[5], smooth muscle tumor, stromal tumor, and lipoma; heterotopic pancreas; and other unusual cases, such as metastatic carcinoma[6], gastric glomus tumor[7],and gastric hamartomatous inverted polyp[8]. According to available reported cases of GC presenting as SMT, the pathologic diagnosis varies including gastric adenocarcinoma[9], gastric mucinous adenocarcinoma[10,11], and gastric lymphoepithelioma-like carcinoma[12].…”
Section: Discussionmentioning
confidence: 99%